The Influence of Motivation, Digital Competence, and Work Environment on the Performance of Employees of the Secretariat of the South Sulawesi Provincial DPRD - Dihaq Allaamah; Roslina Alam; Djamaluddin Bijaang (eCo-Fin, 2025)
This research investigates the impact of work motivation, digital competence, and the work environment on the performance of employees at the South Sulawesi Provincial DPRD Secretariat. Employing a quantitative methodology, the study gathered data through questionnaires distributed to 78 respondents, comprising ASN staff, contract employees, and outsourced workers. The data were analyzed using multiple linear regression techniques, revealing that all independent variables significantly and positively affected employee performance. Digital competence is the most dominant variable, with a contribution of 44%. Each increase of one unit in digital competence has the potential to increase employee performance by 4.04 units. This is supported by the implementation of a digital system that facilitates data management and increases work efficiency. Indicators of data access and use of digital tools are the main contributions in this variable. Work motivation also has a significant effect on performance, especially on indicators of physical, social and self-actualization needs. When basic needs such as salary and facilities are met, and opportunities for potential development are available, employee motivation increases which has an impact on their productivity. The work environment is a key factor in fostering a productive and supportive workplace atmosphere. Indicators of effective communication and a comfortable work atmosphere are the main drivers. Good communication between employees and superiors helps reduce obstacles in completing tasks. In conclusion, developing digital competencies, fulfilling work motivation, and creating a supportive work environment are the main strategies for improving employee performance.